ETMR-01. TREATMENT OUTCOME OF TWO CASES WITH HIGH-GRADE NEUROEPITHELIAL TUMOR WITH BCOR ALTERATION. (4th December 2020) - Kristensen, Ines; Hansen, Louise Lindholt; Mikkelsen, Torben Stamm; Henriksen, Louise Tram; Parm Uldhøi, Benedicte; von Oettingen, Gorm; Cortnum, Søren; Lassen-Ramshad, Yasmin
Abstract: INTRODUCTION: High grade neuroepithelial tumor with BCOR exon 15 internal tandem duplication (HGNET BCOR) is a recently described tumor entity of the central nervous system (CNS) with a distinct methylation profile and characteristic genetic alteration. We report the outcome of two cases after 1 st line multimodality therapy. MATERIAL AND METHOD: A 7 year old girl with a ventricular tumour and a 6 year old boy with a tumour in the occipital region with infiltration of the transverse and sigmoid sinus were both diagnosed based on histology and methylation with HGNET-BCOR. No spinal or liquor dissemination were found at diagnosis in both cases. Treatment consisted of radical resection of the tumour. In the case of the lesion with sinus infiltration residual tumour in the vessel could not be removed. Both children were postoperatively treated with radiotherapy (craniospinal 36 Gy and boost to 54 Gy), concomitant Vincristin and adjuvant Cisplatin, Lomustine and Vincristine. RESULTS: The girl developed a local recurrence at the primary tumour site 18 months after diagnosis. Reoperation showed the same histology. Start of 2 nd line chemotherapy with Temozolomid and Irinotecan is being discussed. The boy with sinus infiltration developed seven months after diagnosis multiple liver, lung and bone metastasis. Biopsy of a liver lesion showed HGNET-BCOR. He was treated with Temozolomid, Irinotecan and died nine months after diagnosis. CONCLUSION: We report two cases with failure after 1 st line treatment for HGNET-BCOR. To our knowledge HGNET-BCOR with development of hematological disease dissemination is a rare finding.